Implementasi Metode Sidayu dalam Meningkatkan Bacaan Al – Qur’an di TK Tarbiyatul Wildan - Ika Ika; Subqi Subqi; Irfanudin Irfanudin; Aisyah Aisyah (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2024)
This research aims to examine the implementation of the Sidayu Method in improving the ability to read the Al-Qur'an in Tarbiyatul Wildan Kindergarten. The Sidayu method is a learning approach that combines various teaching techniques to help children understand and memorize Al-Qur'an reading more effectively. This research uses a qualitative approach with a case study method. Data was collected through observation, interviews and documentation of students and teachers at Tarbiyatul Wildan Kindergarten. The research results show that the application of the Sidayu Method can significantly improve children's ability to read the Al-Qur'an. Children recognize hijaiyah letters more quickly and can read more fluently. Apart from that, this method also makes the learning process more fun and interesting for children. Factors that support the successful implementation of this method include the active involvement of teachers, the use of varied learning media, and support from parents. This research concludes that the Sidayu Method is effective in improving Al-Qur'an reading at kindergarten level. The recommendation for educators is to consider applying this method in Al-Qur'an learning at other basic education levels.